Risk of Peri Implantitis in Patients with Diabetes Mellitus - Yousuf Ahmed Ansari, Muhammad Salman Khan, Sufyan Ahmed, Misbah Shafique, Syed Fahad Ali Shah, Muhammad Haris Zia (Pakistan Journal of Medical & Health Sciences, 2023)
Dental implants have a 97% long-term survival rate; there is no reliable model for predicting implant longevity. Even though it has become more apparent over time and through numerous studies that a variety of patient and professional factors may contribute to peri-implantitis, with compelling theories such as improper three-dimensional (3D) implant placement, poor prosthesis design that interferes with proper oral hygiene practices, and an excess of luting cement, there is no universally accepted diagnostic standard, so prevalence rates are still up for debate. Objectives: This study aims to recognize diabetes for implant loss & peri-implant diseases. It is also intended to measure the prevalence of peri-implant disease 5 years following implant implantation. The study aims to ascertain if implant issues may alter patients’ perceptions of their implants by integrating a patient questionnaire. Methodology: After obtaining the approval of the study from the institution, diabetic patients who had oral implants at the Department of Oral and Maxillofacial Surgery between 2015 and 2020 were added to a list of patients. Following were the criteria for inclusion: Diabetic patients who were older than 18 at the time of consent and comparable radiographs are taken following the first remodeling. There were no prerequisites for the exclusion Results: A total of 165 records were checked to make sure the original radiographs were verified, the implant insertion date, and patient’s contact information. 41 patients met the requirements for inclusion. 36 of the 41 patients who had been contacted and scheduled for a follow-up check showed up (20 male and 16 female, age 34 to 63 yrs; mean – SD age: 47.6 – 10.6 yrs). At baseline, 105 implants were placed in the 36 patients. Conclusion: Because the two disease entities share similar host characteristics or microbiota, diabetes and periodontitis may serve as risk factors for peri-implantitis. Keywords: Dental Implant, Peri-implantitis, Diabetes Mellitus